Pengenalan Digital Marketing bagi Komunitas Kubependa Rawalumbu Bekasi - Ulan Bani, Alexius; Tri Kurnia, Mega (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2022)
Digital marketing has many advantages when compared to conventional marketing strategies, including in terms of measuring the success of a strategy. Digital marketing also makes it easier for business people to monitor and provide all the needs and desires of prospective consumers, and on the other hand, potential consumers can search for and obtain product information only by browsing the virtual world so as to facilitate the search process. Members of the Community of Kubependa Rawalumbu Bekasi, are very interested in the introduction and use of digital marketing for products and in other forms. Mastery of the use of computers and mastery of technology are still lacking and have never received training, especially about digital marketing. The purpose of this service activity is to provide adequate introduction and knowledge of digital marketing. With this training, it is hoped that the trainees will be able to implement and manage the resulting products in business on digital marketing